The Readiness of the Undergraduate Students of the English Tadris Department at UIN Datokarama Palu in Using Google Classroom During Covid-19 Pandemic - Fana Riskiana; Ruslin, Ruslin; Yuni Amelia (English Tadris Department, Tarbiyah and Teacher Training Faculty, Datokarama State Islamic University Palu, 2024)
The spread of the coronavirus outbreak has forced educational institutions to transform learning activities in universities into network-based learning at home. Students unfamiliar with the online learning (google Classroom) system will face various challenges, especially in understanding lessons that cause learning outcomes to be less than optimal. Students' readiness is the first step in accepting and responding to the transformation of learning to achieve their learning goals. The Problems in this research are: (1) How is the readiness of students to implement online learning using Google Classroom? (2) What factors affect student’s readiness to use Google Classroom during the COVID-19 pandemic? It is qualitative descriptive research. The data collection techniques were a questionnaire and an interview. The results indicated that most English students are ready to face online learning using Google Classroom during the COVID-19 pandemic. Four indicators could be used to identify how students were ready for online learning. First, it was the skills of students in using Google Classroom. Second, the students understood how to use technological devices for learning including Google Classroom. Third, the students were ready to receive learning materials through Google Classroom. In addition, the students’ attitudes towards Google Classroom were categorized as sufficiently acceptable. This was shown by the average scores of students, which were 76%. Related to the factors that influenced students’ readiness for online learning, learning facilities and other infrastructures contributed to the readiness of students in learning English via Google Classroom during the Covid-19 Pandemic.